Toward a New Era of SERS and TERS at the Nanometer Scale: From Fundamentals to Innovative Applications - Itoh, Tamitake; Procházka, Marek; Dong, Zhen-Chao; Ji, Wei; Yamamoto, Yuko S; Zhang, Yao; Ozaki, Yukihiro (Chemical reviews, 2023)
Surface-enhanced Raman scattering (SERS) and tip-enhanced Raman scattering (TERS) have opened a variety of exciting research fields. However, although a vast number of applications have been proposed since the two techniques were first reported, none has been applied to real practical use. This calls for an update in the recent fundamental and application studies of SERS and TERS. Thus, the goals and scope of this review are to report new directions and perspectives of SERS and TERS, mainly from the viewpoint of combining their mechanism and application studies. Regarding the recent progress in SERS and TERS, this review discusses four main topics: (1) nanometer to subnanometer plasmonic hotspots for SERS; (2) Ångström resolved TERS; (3) chemical mechanisms, i.e., charge-transfer mechanism of SERS and semiconductor-enhanced Raman scattering; and (4) the creation of a strong bridge between the mechanism studies and applications.